Unpacking the Collection Networks of Material and Social Agency in the Museum - Byrne, Sarah.; Byrne, Sarah.; Clarke, Anne.; Clarke, Anne.; Harrison, Rodney.; Harrison, Rodney.; Torrence, Robin.; Torrence, Robin. (One World Archaeology,, 2011)
Museum collections are often perceived as static entities hidden away in storerooms or trapped behind glass cases. By focusing on the dynamic histories of museum collections, new research reveals their pivotal role in shaping a wide range of social relations.  Over time and across space the interactions between these artefacts and  the  people and institutions who made, traded, collected, researched and  exhibited them have generated complex networks of material and social agency. In this innovative volume, the contributors draw on a broad range of source materials to explore the cross-cultural interactions which have created museum collections. These case studies contribute significantly to the development of new theoretical frameworks to  examine broader questions of materiality, agency, and identity in the past and present.  Grounded in case studies from individual objects and museum  collections from North America, Europe, Africa, the Pacific Islands, and Australia, this truly international volume juxtaposes historical,  geographical, and cross-cultural studies. This work will be of great interest to archaeologists and anthropologists studying material culture, as well as researchers in museum studies and cultural heritage management.